Comparative Evaluation of Suture Techniques in Mitral Valve Replacement: Impact on Clinical Outcomes - Burak Kasapoğlu; Gokay Denız; Sabir Hasanzade; Alp Yıldırım; Serkan Mola (Genel Tıp Dergisi)
Background: This study aimed to compare the outcomes of mitral valve replacement (MVR) using the intermittent simple suture technique versus the horizontal matrix suture technique with pledgeted in terms of paravalvular leakage and infective endocarditis. Methods: A retrospective analysis was conducted on 422 patients who underwent MVR between 2019 and 2023. Patients were divided into two groups based on the suture technique used: group B (simple suture technique) and group P (horizontal matrix suture technique with pledgeted). Propensity score matching was performed to balance the groups, resulting in 62 case pairs for comparative analysis. Results: There were no intraoperative mortalities, and the duration of cardiopulmonary bypass and cross-clamp time did not significantly differ between the two groups. No significant differences were observed in terms of total hospitalization time, early mortality, cerebrovascular events, and arrhythmias. Postoperative echocardiography revealed minimal paravalvular leakage in both groups, with non-serious leakage observed in 4 patients in group B and 2 patients in group P. The incidence of infective endocarditis was 1 in group B and 2 in group P. Hemolysis indicators showed higher mean values in the simple suture technique group, although not statistically significant. Conclusions: The study findings suggest that there is no significant difference in the incidence of paravalvular leak and infective endocarditis between the intermittent simple suture technique and the horizontal matrix suture technique with pledgeted. Both techniques can be safely employed in MVR.